APPLICATION OF AUTONOMOUS LEARNER MODEL IN LEARNING NEWS TEXT (Action Research in Class VIII of MTs Negeri 3 Tasikmalaya) - Hendi Supriyadi (Edusentris, 2022)
Keywords: Writing News Text, Autonomous Learner Model